Application of the Jigsaw Type Cooperative Learning Model with the Guided Discovery Method Used by Prompt Tools on the Surface Area of Curved Sided Template - Findia Ning Tyas, Dewi Kristika (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
Curved-sided geometric shapes have a high level of abstraction, often leading to misconceptions and difficulties in visualizing threedimensional shapes. The Jigsaw cooperative model can enhance interaction and conceptual elaboration through the division of learning roles among students, while the guided discovery method helps students understand concepts and the origins of formulas more deeply. The use of teaching aids also provides concrete experiences that can strengthen visualization and reduce misunderstandings. The synergy of these three approaches has the potential to create more effective, active, and meaningful learning, while meeting the demands of current learning and curriculum that emphasize collaboration, exploration, and conceptual understanding. The study used a qualitative descriptive approach because the purpose of the study was to describe the application of the jigsaw cooperative learning model with the guided discovery method assisted by teaching aids on the surface area of curved-sided geometric shapes. The research subjects were grade IX students. Data were collected through observation, tests, and documentation. Based on the results of observations of student attitude assessments, the percentage of cooperative attitudes was obtained at85,29%, a responsible attitude of83,82%, a self-confident attitude of75%, and a meticulous attitude of75%. . Based on student learning outcomes, the average student score is69,41, and 71% of students met the Minimum Competency Criteria (KKM). These findings confirm that this learning strategy is effective in creating an active and meaningful learning environment